AvalonElite Double Lumen Cannula for Total Cavopulmonary Assist in Failing Fontan Sheep Model with Valved Extracardiac Conduit. Issue 4 (May 2019) - Zhou, Cheng; Wang, Dongfang; Condemi, Francesca; Zhao, Guangfeng; Topaz, Stephen; Ballard-Croft, Cherry; Zwischenberger, Joseph B.
Abstract : The AvalonElite double lumen cannula (DLC) provides total cavopulmonary assist (CPA) in failing Fontan sheep, but recirculation limits reliability. To improve CPA performance, a two-valve extracardiac conduit (ECC) was used to bracket infusion blood toward pulmonary artery (PA). A total cavopulmonary connection with failing Fontan circulation adult sheep model was created with valved ECC (n = 6). The valved ECC was connected to superior/inferior venae cavae (SVC/IVC) and right PA. The AvalonElite DLC was inserted from right jugular vein with infusion opening between the ECC valves. The DLC drainage lumen withdrew blood from SVC/IVC, and the infusion lumen returned blood to ECC. A failing Fontan sheep model with valved ECC was successfully created. Central venous pressure increased from 9 ± 1 to 17 ± 1 mm Hg, systolic arterial pressure decreased from 103 ± 9 to 51 ± 13 mm Hg, and cardiac output decreased from 3.6 ± 0.3 to 1.4 ± 0.2 L/min. Serum lactate significantly increased, indicating poor tissue perfusion. At 4 L/min pumping flow, the AvalonElite DLC returned hemodynamics/lactate to baseline levels throughout 6 hour CPA. Necropsy revealed intact/well-functioning ECC valves and well-positioned DLC with no visible thrombosis. The AvalonElite DLC provides reliable CPA performance in failing Fontan sheep with valved ECC.